2018
DOI: 10.1159/000495205
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Gene Correlation Network Analysis (WGCNA) Detected Loss of MAGI2 Promotes Chronic Kidney Disease (CKD) by Podocyte Damage

Abstract: Background/Aims: Podocyte damage is associated with proteinuria, glomerulosclerosis and decline of renal function. This study aimed to screen critical genes associated with podocyte injury in chronic kidney disease (CKD) by weighted gene correlation network analysis (WGCNA), and explore related functions. Methods: GSE66107, GSE93798, GSE30528, GSE32591 gene expression data including podocyte injury models or glomeruli in CKD patients were downloaded from the GEO database. R was used for data analysis. Differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 51 publications
3
33
0
Order By: Relevance
“…Only 205 genes were unclassified in any module (in grey), accounting for 10.50% of DEGs. In comparison, previous studies have reported an average gene number in each module of 216 to 336 and percentage of genes not found in any module of 5.67%-33.61% of DEGs (Liu X et al, 2017;Liu Z et al, 2018;Yang Q et al, 2018;Zuo Z et al, 2018). In conclusion, our WGCNA results were comparable.…”
Section: Discussionsupporting
confidence: 63%
“…Only 205 genes were unclassified in any module (in grey), accounting for 10.50% of DEGs. In comparison, previous studies have reported an average gene number in each module of 216 to 336 and percentage of genes not found in any module of 5.67%-33.61% of DEGs (Liu X et al, 2017;Liu Z et al, 2018;Yang Q et al, 2018;Zuo Z et al, 2018). In conclusion, our WGCNA results were comparable.…”
Section: Discussionsupporting
confidence: 63%
“…32 Other studies also have revealed that MAGI-2 genetic mutation leads to a severe renal phenotype in mice and humans. 30,[33][34][35][36] J o u r n a l P r e -p r o o f However, an understanding of the mechanism underlying the phenotype has remained elusive. In particular, although the SD in podocytes is crucial as a kidney filtration barrier, it is unclear whether MAGI-2 interacts with the SD.…”
Section: Introductionmentioning
confidence: 99%
“…21 Based on the WGCNA, the module with a high correlation with the disease progression would be screened out. 29,30 The dysregulated genes in the module are usually defined as hub genes that are involved in the pathogenesis of disease. 29,30 In the present study, the differentially expressed lncRNAs and mRNAs were divided into nine modules.…”
Section: Knockdown Of Nonratt0107882 Inhibits Neuronal Apoptosismentioning
confidence: 99%
“…29,30 The dysregulated genes in the module are usually defined as hub genes that are involved in the pathogenesis of disease. 29,30 In the present study, the differentially expressed lncRNAs and mRNAs were divided into nine modules. There was a strong correlation between SE and two modules (brown module and turquoise module).…”
Section: Knockdown Of Nonratt0107882 Inhibits Neuronal Apoptosismentioning
confidence: 99%